2016
DOI: 10.1111/tid.12592
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in human immunodeficiency virus‐infected recipients: a case–control study from the Brazilian experience

Abstract: In the Brazilian experience, despite somewhat inferior outcomes, kidney transplantation is an adequate therapy for selected HIV-infected recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…It is possible that worse donor maintenance conditions, already reported in a recent analysis, and the longer cold ischemia time in the Brazilian cohort had influenced this outcome, although the small sample size precludes drawing definitive conclusions. However, the recent finding that Brazilian patients with HIV infection have higher occurrence of DGF when compared with their seronegative counterparts, in accordance with previous published studies, suggests that mechanisms still undiscovered may influence this outcome.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is possible that worse donor maintenance conditions, already reported in a recent analysis, and the longer cold ischemia time in the Brazilian cohort had influenced this outcome, although the small sample size precludes drawing definitive conclusions. However, the recent finding that Brazilian patients with HIV infection have higher occurrence of DGF when compared with their seronegative counterparts, in accordance with previous published studies, suggests that mechanisms still undiscovered may influence this outcome.…”
Section: Discussionsupporting
confidence: 86%
“…who described a successful outcome in two Brazilian recipients with well‐controlled HIV infection. Recently, a Brazilian study demonstrated inferior outcomes of patients with HIV infection when compared to a paired HIV‐negative population, with higher incidence of delayed graft function (DGF), AR, surgical complications leading to graft loss, and infection‐related recipient deaths …”
Section: Introductionmentioning
confidence: 99%
“…While HIV infection was previously considered a contraindication to transplantation due to concern for opportunistic infections and early reports of poor patient and allograft survival, today HIV + transplant recipients demonstrate allograft survival rates similar to their HIV‐ counterparts and improved survival relative to patients remaining on dialysis 2,3 . Despite improvements in HIV + transplant outcomes, rates of acute rejection and infectious complications remain higher than those observed in the general transplant population, and selection of the optimal immunosuppression strategy remains challenging 3‐5 . Since publication of the landmark trial by Stock et al, standard maintenance immunosuppression for HIV + transplant recipients has generally consisted of tacrolimus, mycophenolate mofetil (MMF), and tapering corticosteroids 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the recent positive experience with carefully selected South‐African HIV‐infected patients who received kidneys from HIV‐infected donors prompted changes to the US’ legislation, allowing the development of clinical research and eventually a revision of the organ donation and transplantation regulation . In many aspects, however, SOT recipients with HIV‐infection differ from non‐HIV infected subjects, as they present an increased rate of delayed graft function, challenging drug‐to‐drug interactions, and higher rates of acute allograft rejection and infectious complications …”
Section: Introductionmentioning
confidence: 99%
“…6 In many aspects, however, SOT recipients with HIV-infection differ from non-HIV infected subjects, as they present an increased rate of delayed graft function, challenging drug-to-drug interactions, and higher rates of acute allograft rejection and infectious complications. 1,7,8 HIV infection through transfusion of contaminated blood components has been repeatedly documented since the first case reported in 1982, 9 and has also been documented among organ transplant recipients, primarily in the 1980s and early 1990s. [10][11][12][13] Since 1985, the adoption of strict measures for collecting, testing and processing blood components has resulted in a significant reduction in this route of transmission, now reported as residual risks of one per 8-24 million donations.…”
mentioning
confidence: 99%